2014
DOI: 10.1016/j.neuron.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

FLRT Structure: Balancing Repulsion and Cell Adhesion in Cortical and Vascular Development

Abstract: SummaryFLRTs are broadly expressed proteins with the unique property of acting as homophilic cell adhesion molecules and as heterophilic repulsive ligands of Unc5/Netrin receptors. How these functions direct cell behavior and the molecular mechanisms involved remain largely unclear. Here we use X-ray crystallography to reveal the distinct structural bases for FLRT-mediated cell adhesion and repulsion in neurons. We apply this knowledge to elucidate FLRT functions during cortical development. We show that FLRTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
242
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(259 citation statements)
references
References 55 publications
17
242
0
Order By: Relevance
“…S1), yielding heterophilic K D s ranging between 3.6 and 43.9 μM (Fig. 1C), similar to the affinities of other tight-binding cell adhesion molecules (22)(23)(24)(25)(26)(27)(28). Interestingly, the strongest-binding pairs (Dsg1:Dsc1 and Dsg4:Dsc1) correspond to those expressed in the outermost layers of human skin, and the weakest (Dsg3:Dsc3) to those restricted to basal layers (1,10), consistent with a potential role for differential affinities in maintenance of cell arrangement in stratified epithelia (1).…”
Section: Significancesupporting
confidence: 62%
“…S1), yielding heterophilic K D s ranging between 3.6 and 43.9 μM (Fig. 1C), similar to the affinities of other tight-binding cell adhesion molecules (22)(23)(24)(25)(26)(27)(28). Interestingly, the strongest-binding pairs (Dsg1:Dsc1 and Dsg4:Dsc1) correspond to those expressed in the outermost layers of human skin, and the weakest (Dsg3:Dsc3) to those restricted to basal layers (1,10), consistent with a potential role for differential affinities in maintenance of cell arrangement in stratified epithelia (1).…”
Section: Significancesupporting
confidence: 62%
“…Transmembrane FLRT2 proteins are proteolytically cleaved to release soluble ectodomains (Seiradake et al, 2014;Yamagishi et al, 2011) that diffuse into the extracellular spaces. Thus, it is likely that one FLRT2-expressing endothelial cell acts repulsively on multiple UNC5B-expressing cells, both in paracrine and autocrine manners.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, X-ray crystallography (Seiradake et al, 2014) revealed that FLRT2 binds to FLRT2 (homophilic binding) as well as to UNC5B, UNC5C and UNC5D (heterophilic binding) via different extracellular regions of FLRT2 (Fig. 5A).…”
Section: Flrt2 Repulses Endothelial Cells In Vitro Through the Unc5b mentioning
confidence: 94%
See 2 more Smart Citations